PENGARUH PENERAPAN STRATEGI PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 PULAU PUNJUNG - Rahmah, Miftahul; ZA, Nilawasti; Zulfaneti, Zulfaneti (Pendidikan Matematika, 2013)
The background of this research is the students comprehension of matematical concept that still low. This result of students math study at  eight grade Junior Hight School 1 Pulau Punjung. The purpose this research is to know the comprehension matematical concepts of student that apply Problem Based Learning strategy is better than comprehension mathematical consept that applied teaching conventional in eight class Junior Hight School. The kinds of research is experimental research, with planning research random to subject. The population of  this research is eight grade students of Junior Hight School 1 Pulau Punjung except grade VIII1 academic year 2013/2014 which consists of six classes. Technique of random sampling. The instrument used in this study is test of comperehension mathematical concepts. From of test used is a form to essay with a reliabilitty tes r11 = 0,987. The data analysis  technique used is one the t-test . Based on the analysis of the data found that the normal distribution of the sample class L0 = 0,1319 dan Ltabel = 0,1542. Hyphothesis test result obtained taccount < , then the hypothesis in this study received. The conclusion of this reseachs is  the students comprehension of mathematical concept that apply Problem Based Learning strategy better than the comprehension mathematical concept that students apply classroom learning in the conventional at Junior Hight School.